A special section on big data technology and information management in medical and health informatics - Wang, Defeng (2019)
In our modern world, health informatics is the inevitable development trend of the medical industry. From the individual patient information query to the allocation of thousands of resources and staff, all the information operations involved is a part of the process of informatics. In the past few decades, the computing hardware and software has continued to grow exponentially. Furthermore, breakthrough in operational research and arrival of the era of big data has helped us to find a better solution for human information needs. However, there still are some challenging problems for providing a better service. For most given problems, multi-objective optimization and data mining can provide the optimal solution. And machine learning such as artificial neural network, deep learning, evolutionary algorithm, and genetic algorithm are some of the other well-established techniques we can explore for solutions generation. In the medical industry, using these algorithms can help hospital finds the potential factors which affect patients’ health more accurately and improve diagnosis. It can also identify health trends that bridge the gaps among fragments of seemingly unrelated information. In addition, the process of information management also promotes the development of bioinformatics, including membrane computing, gene expressions, genetic computing, etc. These new technologies can offer much higher quality and personalized service for patients.